2010
DOI: 10.1007/s00221-010-2507-9
|View full text |Cite
|
Sign up to set email alerts
|

Stroop matching task: role of feature selection and temporal modulation

Abstract: We conducted an event-related potential (ERP) study to investigate the electrocortical dynamics of attentional feature-based processing in the Stroop matching task. Participants in the study (n = 37) compared the ink color of a colored word with the meaning of a color-word in white ink. The two task stimuli were presented simultaneously or with SOAs (Stimulus Onset Asynchrony) of 400 and 1,200 ms. The Stroop matching effect was maximal during SOA-0, was reduced at SOA-400, and was inverted at SOA-1200. We focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…An event-related potential study found that feature selection plays an important role in the Stroop matching task. This attentional feature selection, reflected by the N1 component amplitude, was influenced by Stimulus Onset Asynchrony (SOA) manipulation and markedly correlated with the behavioral results (for details, see David et al, 2011). Therefore, the Stroop matching task constitutes a useful tool for exploring the effects of alcohol on feature selection under conflict.…”
Section: Introductionmentioning
confidence: 74%
“…An event-related potential study found that feature selection plays an important role in the Stroop matching task. This attentional feature selection, reflected by the N1 component amplitude, was influenced by Stimulus Onset Asynchrony (SOA) manipulation and markedly correlated with the behavioral results (for details, see David et al, 2011). Therefore, the Stroop matching task constitutes a useful tool for exploring the effects of alcohol on feature selection under conflict.…”
Section: Introductionmentioning
confidence: 74%
“…Moreover, the slightly enhanced stimulus interference in the Flanker task of Experiment 2 (adopting the same design with Experiment 1) also conflicts with the proportion interpretation. In addition, one previous study finds that a facilitation from the distractor enhances the early processing of the target stimulus [37]. However, if the participants tend to make a response based on word reading, larger response interference will be observed in Experiment 1 because word reading facilitates color naming in the SI trials but interferes with that in the RI trials.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we did not discard the possibility that nonresponse conflicts, other than semantic conflict, are involved. In a recent Stroop matching task ERP study, an early facilitation was demonstrated during the “same” responses for the congruent/related condition compared to the incongruent/unrelated condition, which was reflected by the N1 amplitude (David et al., ). It was suggested that when relevant and irrelevant attributes are in the same feature domain (e.g., both are colors in the case of a word–color matching), distracter‐color processing could induce irrelevant matching and a conflict in other stages of processing (David et al., ; Goldfarb & Henik, ).…”
Section: Discussionmentioning
confidence: 97%
“…In a recent Stroop matching task ERP study, an early facilitation was demonstrated during the “same” responses for the congruent/related condition compared to the incongruent/unrelated condition, which was reflected by the N1 amplitude (David et al., ). It was suggested that when relevant and irrelevant attributes are in the same feature domain (e.g., both are colors in the case of a word–color matching), distracter‐color processing could induce irrelevant matching and a conflict in other stages of processing (David et al., ; Goldfarb & Henik, ). During the conditions in which the target‐color (bar color surface) and the distracter‐color (word color surface) are related, the comparison is facilitated by the fact that the distracter‐color and the target‐color are the same.…”
Section: Discussionmentioning
confidence: 97%